Construction of a physical fitness evaluation index system and model for high-level freestyle skiing aerials athletes in China - Yao, Y.; Niu, X. (PLOS ONE, 2023)
Objective This study aims to enhance the competitive level of Chinese freestyle skiing aerials athletes by developing a specialized physical fitness evaluation index system and model tailored for high-level Chinese athletes. This system intends to provide theoretical references and training monitoring schemes in preparation for the 25th Milan Winter Olympics.